Antecedents of customer loyalty and performance improvement: Evidence from Pakistan's telecommunications sector. (June 2021) - Shahzad, Arfan; Yaqub, Rana Muhammad Shahid; Di Vaio, Assunta; Hassan, Rohail
Abstract: The paper investigates and compares different groups of customers (stayers and switchers) in terms of antecedents of customer loyalty in the telecommunications (telecom) sector, specifically, customer satisfaction, perceived service quality, perceived price fairness, perceived justice in service recovery, and relational bonds. The data were analyzed through the PLS-SEM Approach. The results revealed significant differences between both groups (i.e., stayers and switchers) in their sense of loyalty antecedents. These differences impact the performance of the telecommunications sector in economic, environmental, and social terms. However, the study revealed no difference between stayers and switchers perceptions of service quality. Our research makes a significant theoretical contribution to the consumer behavior literature by comparing stayers and switchers in the telecommunications sector. Moreover, the study has also offered various practical contributions for managers and practitioners to devise value-based strategies for both groups. Highlights: This study analyzed different groups of customer's perceptions (stayers & switchers) in the telecommunication sector. This study highlights the importance of the analysis to improve economic, environmental and social performance. The study provides practical contributions for managers and practitioners. Partial least square structural equation modeling (PLS-SEM) was employed for data analysis. The results revealed significant differences between both groups (stayers & switchers).